Gold production in the Superior Province of the Canadian Shield - C. H. Bertoni (Canadian Institute of Mining, Metallurgy and Petroleum, 1983)
"The Superior Province of the Canadian Shield is the largest gold producing area within Archean greenstone rocks in the world, with total production of over 140 million ounces of gold. One hundred and fifty-five mines have individually produced more than 8,000 ounces, although only a relatively limited number of deposits (33) produced more than one million ounces of gold. The output from these 33 deposits accounts, however, for 85% of total gold production. The majority of grades (68%) ranges between 0.10 and 0.30 ounce per ton, and there is no linear relationship between grade and tonnage.Development of new gold mines reflects the history of gold prices. However, the response to the latest increase in gold prices was not as marked. It is concluded that gold deposits are becoming increasingly more difficult to find and new exploration techniques are urgently required.IntroductionWith most of its production coming out of the Superior Province, the Canadian Shield is the largest producer of gold from Archean greenstone rock s in the world. In total gold production, the Superior Province is surpassed only by the paleo-placers of Witwatersrand and the placers of the USSR (Anhaeusser, 1976). There has been no attempt so far to compile the historical production of the Province as a whole in a single document. The aim of this work is to fill this gap, not only for the convenience of having a complete list of gold producers, but, more importantly, as a basis on which to study the tonnage and grade characteristics of these deposits."